Separation anxiety dalam kalangan kanak-kanak daripada perspektif ibubapa - Nur Qhaizrunissa Uzma, binti Daud (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to identify separation anxiety among children from the perspective of parents in Kampung Kanchong Baru, Gedong, Sarawak. The main objective of this study is to identify causes, symptoms and behaviors of separation anxiety among children from the perspective of the parent. This study employed qualitative methods, which was interview-method. The results ofthe pilot study carried out to ensure a set of questions to be asked to the participants in the real study. The researcher interviewed three participants whom parent to children who suffer from separation anxiety. The fmding showed that every child suffers the causes, symptoms and behaviors that vary from the perspective of the parent. However, there are also some similirities in term of the causes, symptoms and behaviors of children who suffer from separation anxiety. Therefore, this study brings awareness to the parents to be more sensitive to their child and parent should know how to overcome the separation anxiety in their children.